(untitled) (Research, Society and Development, 2026)
This study aimed to evaluate the effects of different cotton production systems on the soil water infiltration rate in a sandy Red-Yellow Latosol in Luís Eduardo Magalhães, Bahia, after seven years of cultivation. The quantitative and experimental research used a randomized block design with six management systems: monoculture and succession (conventional tillage) and four crop rotations under a no-tillage system (SPD), plus a native Cerrado area as a control. Infiltration was determined using the double-ring infiltrometer method. Results indicated that the native Cerrado had the highest stable infiltration rate (Tie) (34.8 cm h⁻¹), while all agricultural systems significantly reduced this capacity. Among the crops, the conventional system with millet/cotton succession achieved the highest Tie (16.0 cm h⁻¹), surpassing the SPD treatments. This is attributed to mechanical tillage that temporarily increases porosity in sandy soils, although this structure is unstable and subject to rapid rearrangement. In SPD, rotations including legumes were superior to exclusive cereal rotations, highlighting the importance of root diversification for improving biopores. It is concluded that land use severely impacts water dynamics, with the maintenance of native areas and the adoption of complex rotations being fundamental for the sustainability of cotton farming and aquifer recharge in the Bahia Cerrado.